Analysis of Escherichia coli isolated from bovine mastitic milk - Rangel, Patricia [UNESP]; Marin, Jose Moacir (Revista Pesquisa Veterinaria Brasileira, 2009)
Rangel P. & Marin J.M. 2009. Analysis of Escherichia coli isolated from bovine mastitic milk. Pesquisa Veterinaria Brasileira 29(5): 363-368. Departamento de Morfologia, Estomatologia e Fisiologia, Faculdade de Odontologia de Ribeirao Preto, Universidade de São Paulo, Avenida do Cafe s/n, Campus USP, Ribeirao Preto, SP 14040-904, Brazil. E-mail: jmmarin@forp.usp.brMastitis has been recognized for some time as the most costly disease in dairy herds. From February to November 2004, 670 samples of bovine mastitic milk from which 231 Escherichia coli strains were isolated, were collected from two Brazilian states. The strains were screened for the presence of Shiga toxin-producing (stx 1 and stx 2) and intimin (eae) genes. Twenty (8.6%) strains were detected by PCR to harbor the Shiga toxin genes (8 the stx 1 gene, 12 the stx 2 gene and none both of them). Two (0.8%) of the Escherichia coli strains studied were eae positive non Shiga toxin-producing. The strains were also examined for resistance to 12 antimicrobial agents. The predominantly observed resistance was to tetracycline (92.2%), streptomycin (90.4%), nalidixic acid (88.3%), amikacin (86.5%) and cephalothin (84.8%). Multidrug resistance was found among 152 isolates (65.8%).
Keywords: Escherichia coli; mastitis; antimicrobial agents; multidrug resistance; STEC; eae gene